Sumatera Task Force - A Field Report of Final-Year Medical Student Deployment in Flash Flood Disaster Response - Arohid Allatib; Hazel Fairuz Shidqi; Abdul Aziz Maulana Ilmi; Muhammad Rakan Kabbani; Rafif Muzakki; Dian Andriani Ratna Dewi (The ASEAN Journal of Military and Preventive Medicine, 2026)
Background: Flash floods are a recurrent public health crisis in Indonesia, causing acute morbidity in communities with limited healthcare access. Final-year medical students represent a potentially valuable yet underutilized workforce in disaster response. This study describes the deployment of the Padang Task Force—25 final-year medical students from Universitas Pertahanan Republik Indonesia (UNHAN)—during flash flood response in Aceh Tamiang, Aceh (11–18 December 2025). Methods: A qualitative descriptive field report with narrative literature review. Data were obtained from patient records, operational logbooks, and field observations during the 7-day deployment. Clinical activities were supervised by specialists from the National Defense Central Hospital (RSPPN) and Tri Matra military physicians. Results: Approximately 240 patients were treated daily (estimated 3,840 total encounters). Predominant conditions included upper respiratory tract infections (URTIs), dermatophyte infections, scabies, acute diarrhea, and traumatic wounds. Key challenges included infrastructure collapse, medication shortages, absent laboratory support, and regulatory gaps regarding unlicensed student practice. Conclusion: Supervised deployment of final-year medical students is feasible and effective in resource-constrained disaster settings. Formal regulatory frameworks, improved logistics planning, and integrated disaster medicine curricula are needed to optimize future responses.